2009
DOI: 10.3171/2008.6.17620
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic evaluation of trigeminal neurovascular compression in patients with and without trigeminal neuralgia

Abstract: Trigeminal NVC occurs in asymptomatic patients but is more severe and more proximal in patients with TN. This information may help identify patients who are likely to benefit from microvascular decompression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
78
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(87 citation statements)
references
References 34 publications
6
78
0
3
Order By: Relevance
“…However, analysis of anatomical and clinical data supports our concept that at the level of the brainstem, when leaving the trigeminal root, specifically at the REZ, the sensory fibers change their direction to target their proper nuclei in the trigeminal brainstem nuclear sensory complex (TBNSC) (Crissman et al, 1996;Pajot et al, 2000;Devor et al, 2002b;Sindou et al, 2002Sindou et al, , 2006Miller et al, 2009). Consequently, many of the Aβ fibers transmitting tactile information from the orofacial region leave the trigeminal root rostrally in their trajectory to the main sensory nucleus, located at the level of the midpons (Samii and Jannetta, 1981;Sessle, 2000) (Fig.…”
mentioning
confidence: 94%
“…However, analysis of anatomical and clinical data supports our concept that at the level of the brainstem, when leaving the trigeminal root, specifically at the REZ, the sensory fibers change their direction to target their proper nuclei in the trigeminal brainstem nuclear sensory complex (TBNSC) (Crissman et al, 1996;Pajot et al, 2000;Devor et al, 2002b;Sindou et al, 2002Sindou et al, , 2006Miller et al, 2009). Consequently, many of the Aβ fibers transmitting tactile information from the orofacial region leave the trigeminal root rostrally in their trajectory to the main sensory nucleus, located at the level of the midpons (Samii and Jannetta, 1981;Sessle, 2000) (Fig.…”
mentioning
confidence: 94%
“…Magnetic resonance imaging (BFFE and MRA) using a 3-T MR scanner (Philips Achieva) was performed as previously described. 34,35 The 3D reconstructions were independently reviewed by a neurosurgical fellow blinded to the surgical findings.…”
Section: Imagingmentioning
confidence: 99%
“…We have previously demonstrated that 17% of the general population manifests NVC of the trigeminal nerve. 35 If, as has been estimated, the incidence of TN in the population is 1:10,000 (0.01%), 32 then 99.94% of individuals with trigeminal NVC do not have TN. Given these statistics, and the present evidence that TN can both occur and recur without NVC, the hypothesis that TN is caused by neurovascular conflict must be challenged.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…8,10,13,21 Structural changes in the trigeminal nerve, leading to volume loss, have been well documented, 3,6,12 and a number of studies have demonstrated that nerve atrophy ipsilateral to the symptomatic side is visible on preoperative MRI. 1,4,5,7,9,15,17 Recently, Leal et al demonstrated that atrophy in the midcisternal region of the nerve is associated with more severe vascular compression, and these patients tend to exhibit greater clinical improvement following surgical decompression of the nerve. 10 However, it is unclear whether the nerve atrophy is entirely due to physical compaction by the compressing vessel or whether it is due, in part, to irreversible structural changes.…”
mentioning
confidence: 99%